A Foresight Study of Metaverse Technology Adoption in Training and Development among Employees in Electrical and Electronics Industries - Azahar, Aida Farhana; Rodzalan, Shazaitul Azreen (Research in Management of Technology and Business, 2025)
Training and development were critical in human resource management for enhancing employee skills and competencies. This study was conducted to explore the potential of using Metaverse technology for employee training in the Electrical and Electronics Industries, focusing on the challenges, key drivers, and future applications. Traditional training methods often failed to meet the industry’s evolving demands, necessitating innovative approaches. This research investigated the challenges, trends, and opportunities of adopting Metaverse technology in training programs. Using a mixed-methods approach, insights from HR professionals in Penang, Malaysia, were collected to understand the feasibility and effectiveness of Metaverse integration. The results identified the main drivers for adoption, which were assessing its impact on skill development and envisioning future applications in training programs. The significance of this study lay in its potential to enhance employee engagement, job satisfaction, and overall performance through immersive learning experiences. By addressing the benefits and challenges of Metaverse technology, this research aimed to provide practical insights for organizations to remain competitive and innovative, driving sustainable growth and global competitiveness in the manufacturing electrical and electronics sector.